Penerapan Metode Demonstrasi Dalam Meningkatkan Pemahaman Siswa Pada Materi Perawatan Jenazah - Moh. Tauhid; Alifah Wulandari (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
There are fewer and fewer people who understand the theory and practice of treating corpses. This can be found when there is a deadly accident, people have difficulty caring for corpses. Therefore an understanding of corpse care needs to be instilled from school age to the next generation. This study aimed to increase students' understanding of corpse care material using the demonstration method at SMA Negeri 1 North Sangatta. The method used in this research is a class action research method. The results show that the use of the demonstration method can increase students' understanding of corpse care material. This was marked by an increase of 25%, from 70% to 95% after the action was taken. In addition, students' enthusiasm for learning increased during learning when using the demonstration method. Furthermore, the demonstration method can also provide new experiences and give a deep impression to students because they directly demonstrate the care of corpses.